2013
DOI: 10.1007/s10803-013-1886-8
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Limit to the Superiority of Individuals with ASD in Visual Search?

Abstract: Superiority in visual search for individuals diagnosed with autism spectrum disorder (ASD) is a wellreported finding. We administered two visual search tasks to individuals with ASD and matched controls. One showed no difference between the groups, and one did show the expected superior performance for individuals with ASD. These results offer an explanation, formulated in terms of load theory. We suggest that there is a limit to the superiority in visual search for individuals with ASD, related to the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…That accelerated search is more pronounced in absent trials has been noted in the earliest research examining visual search in ASD (O’Riordan et al, 2001), and while multiple studies have since reported a similar finding (Hessels et al, 2014; Joseph et al, 2009; O’Riordan, 2000; O’Riordan & Plaisted, 2001), it remains unknown as to why this is the case. What is it about autistic attentional or perceptual processes that convey this advantage for target absent trials?…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…That accelerated search is more pronounced in absent trials has been noted in the earliest research examining visual search in ASD (O’Riordan et al, 2001), and while multiple studies have since reported a similar finding (Hessels et al, 2014; Joseph et al, 2009; O’Riordan, 2000; O’Riordan & Plaisted, 2001), it remains unknown as to why this is the case. What is it about autistic attentional or perceptual processes that convey this advantage for target absent trials?…”
Section: Discussionmentioning
confidence: 85%
“…This disparity in performance generally becomes larger as target-distractor similarity increases (O’Riordan, 2004; O’Riordan & Plaisted, 2001; O’Riordan, Plaisted, Driver, & Baron-Cohen, 2001; Plaisted, O’Riordan, & Baron-Cohen, 1998; see Hessels, Hooge, Snijders, & Kemner, 2014, for conflicting findings), as set size increases, and when the target is absent (Kaldy et al, 2013). Evidence of augmented ASD search superiority with increasing target-distractor similarity has been used to support the hypothesis that enhanced discrimination contributes to faster search (O’Riordan & Plaisted, 2001), which is consistent with the more general concept of enhanced perceptual functioning (Mottron, Dawson, Soulieres, Hubert, & Burack, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Remington et al found that high perceptual load reduced distractor interference in normal adults but not in people with ASD. Further studies have shown that under extremely high perceptual load, there is no difference between ASD participants and controls (Hessels, Hooge, Snijders, & Kemner, 2014). Children with autism have been found to be less susceptible to inattentional blindness than controls, and whereas increases in perceptual load are associated with increased inattentional blindness in controls, children with autism were unaffected by load increases (Swettenham et al, 2014).…”
Section: Individual Differences Under Loadmentioning
confidence: 97%
“…The procedure and stimuli were similar to previous studies, which have reported superior search in ASD [Hessels, Hooge, Snijders, & Kemner, 2014;Kemner, Van Ewijk, Van Engeland, & Hooge, 2008;O'Riordan & Plaisted, 2001]. The target was a vertical line and the distractors were oblique lines (tilted 10 ; Fig.…”
Section: Visual Search Taskmentioning
confidence: 99%